Fe-based catalyst for synthesizing formic acid under mild condition and preparation method of Fe-based catalyst
By introducing Fe into pure silicon molecular sieve, Fe-based catalysts for methane oxidation under mild conditions were prepared, which solved the problem of easy poisoning of the active surface of the catalyst at low temperatures, and achieved efficient formic acid generation and good cycle stability.
Patent Information
- Application Number
- CN202411744899.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Designing highly active methane oxidation catalysts to synthesize formic acid under mild conditions is a challenge, especially at low temperatures where the active surface of the catalyst is easily poisoned by oxygen or hydrogen peroxide.
By dissolution and re-crystallization, Fe is introduced into the pure silicon molecular sieve framework and pores to prepare a Fe-based catalyst for oxidizing methane into formic acid under mild conditions.
The efficient selective oxidation of methane in methane to synthesize formic acid under mild conditions (70 °C), the catalyst showed excellent formic acid generation activity and good cycle stability.
Smart Images

Figure CN119549193A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and particularly relates to an Fe-based catalyst for synthesizing formic acid under mild conditions and a preparation method thereof. Background Art
[0002] Methane is the simplest hydrocarbon and is widely distributed in mineral resources and biomass resources such as natural gas, shale gas, coalbed methane, biogas, refinery gas, and methane hydrate (combustible ice). Natural gas refers to a naturally formed flammable mixed hydrocarbon and non-hydrocarbon gas stored under the surface of the earth. The main component is methane, which accounts for about 80-90%. There are also small amounts of ethane, propane and butane, as well as a small amount of carbon monoxide and trace amounts of rare gases. Natural gas is a clean energy source. The development and utilization of natural gas can reduce the use of coal and oil, thereby improving the quality of the air and occupying an important position in the world's energy structure. The methane molecule has a stable tetrahedral structure. The central carbon atom reacts with four hydrogen atoms to form a SP 3 Hybridization forms four identical carbon and hydrogen bonds. Under standard conditions, the bond cleavage energy of the first CH bond of methane can reach 439.3 kJ·mol -1 , its CH bond energy is the highest among all alkanes. At the same time, methane has high ionization energy, low proton affinity, acidity, and a large HOMO / LUMO energy level difference. This means that methane is a fairly stable molecule and requires very intense reaction conditions such as high temperature and strong acid to be activated. Therefore, achieving the activation and selective conversion of CH4 under mild conditions is a global problem.
[0003] At present, the pathways for converting methane into high-value-added chemicals and liquid fuels are mainly divided into two categories: indirect conversion and direct conversion. The indirect process relies on obtaining synthesis gas (CO and H2) through reforming reactions or through partial oxidation, and producing other high-value-added chemicals through technologies such as Fischer-Tropsch synthesis or alcohol synthesis. There are many reactions for the direct conversion of methane, such as oxidative coupling to ethylene (OCM), formaldehyde and methane oxygen-free aromatization. Direct methane conversion has the advantages of short process flow, low energy consumption and low cost. However, it is still a challenge to design highly active catalysts for CH4 oxidation to organic oxygen-containing compounds under mild conditions. The reason is that the active surface of the catalyst used for CH4 oxidation is easily poisoned by oxygen or hydrogen peroxide oxidation at low temperatures. Even at low temperatures, O2 and H2O can easily deactivate the catalytic center through immediate oxidation of the supported metal clusters. From this point of view, encapsulating the active center in a microporous environment is a better choice for CH4 oxidation conversion under mild conditions. In fact, among the catalysts that catalyze CH4 conversion under mild conditions, the catalytic centers of most catalysts are metal atoms or metal oxygen clusters in MOFs (ACS Catal., 2022, 12, 11159) coated in the micropores of silica-alumina molecular sieves, such as ZSM-5 (J. Am. Chem. Soc., 2023, 145, 5888), SSZ-13 (Fuel, 2022, 309,122178) and MOR (J. Am. Chem. Soc., 2023, 145 (23): 12928). However, the introduction of Al limits the subsequent Fe content and may promote side reactions such as dehydrogenation of ethane / propane and dry reforming of methane. Therefore, pure silica zeolite is an ideal carrier for methane oxidation catalysts. The present invention increases the Fe content in the molecular sieve by dissolution and re-crystallization and is successfully used in methane oxidation reactions. Summary of the invention
[0004] The purpose of the present invention is to provide an Fe-based catalyst for synthesizing formic acid under mild conditions and a preparation method thereof, wherein Fe is introduced into the framework and pores of a pure silicon molecular sieve to obtain an Fe-based catalyst for oxidizing methane to formic acid under mild conditions (70 °C).
[0005] To achieve the above object, the present invention adopts the following technical solution: A method for preparing an Fe-based catalyst for synthesizing formic acid under mild conditions comprises the following steps: (1) Pure Si molecular sieve, template and water are mixed, subjected to high temperature hydrothermal treatment to obtain a precursor sol, and then cooled to room temperature; (2) slowly introducing an aqueous solution containing an Fe source into the precursor sol, stirring it evenly, and then subjecting it to high-temperature hydrothermal treatment for crystallization again; (3) The solution obtained in step (2) is centrifuged, washed and dried, ground into powder and then calcined in a high temperature atmosphere to obtain an Fe-based catalyst.
[0006] Furthermore, the topological structure of the pure Si molecular sieve in step (1) is any one of MFI, BEA and CHA.
[0007] Furthermore, the template agent in step (1) is one of tetrapropylammonium hydroxide, tetraethylammonium hydroxide and N,N,N-trimethyladamantanammonium hydroxide.
[0008] Furthermore, in step (1), the molar ratio of pure Si molecular sieve, template and water is 1: (0.2-2.0): (10-50).
[0009] Furthermore, the hydrothermal treatment temperature in step (1) is 100-230 o C, the hydrothermal treatment time is 3-6 h.
[0010] Furthermore, the hydrothermal treatment temperature in step (2) is 140-230 o C, the time of high temperature hydrothermal treatment is 24-72h.
[0011] Furthermore, the Fe source in step (2) is one of Fe(NO3)3·9H2O, FeCl3·6H2O or EDTA-Fe.
[0012] Furthermore, the calcination temperature in step (3) is 450-900 °C and the calcination time is 6-12 h.
[0013] The Fe-based catalyst obtained by the preparation method is used for synthesizing formic acid under mild conditions.
[0014] The Fe content in the Fe-based catalyst is 0.1-1.5 wt %.
[0015] An application of the Fe-based catalyst in the selective oxidation of methane to synthesize formic acid.
[0016] Beneficial effects of the present invention: (1) The present invention successfully implants highly dispersed Fe into the framework and pores of the molecular sieve through a synthesis method of dissolution and secondary crystallization, and exhibits excellent formic acid production activity in the selective oxidation of methane to formic acid.
[0017] (2) The pure Si-type Fe-based catalyst prepared in the present invention has high activity under mild conditions, providing a highly efficient catalyst for the technology of selective oxidation of methane to prepare formic acid, thereby promoting the further development of the technology of selective oxidation of methane. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The XRD diagrams of the catalysts obtained in Example 1 and Comparative Example 1 are shown.
[0019] Figure 2 The UV-Vis graphs of the catalysts obtained in Example 1 and Comparative Example 1 are shown.
[0020] Figure 3 TEM images of the catalysts obtained in Example 1 (A) and Comparative Example 1 (B); red represents Fe element, cyan represents O element, and green represents Si element.
[0021] Figure 4 The CH4-TPD diagrams of the catalysts obtained in Example 1 and Comparative Example 2 are shown.
[0022] Figure 5 This is the XRD diagram of the catalyst obtained in Example 1 before and after the reaction.
[0023] Figure 6 This is the UV-Vis graph of the catalyst obtained in Example 1 before and after the reaction.
[0024] Figure 7 This is a graph for evaluating the cyclic stability of the catalyst obtained in Example 1. DETAILED DESCRIPTION
[0025] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0026] Example 1 0.5Fe-MFI After mixing and stirring 4.48 g of tetrapropylammonium hydroxide and 39.63 g of water, slowly add 25.51 g of tetraethyl orthosilicate and continue stirring until it is clear and transparent. Then, stir the above solution in a 50 °C water bath for 30 min, then raise the temperature to 80 °C and stir continuously to drive away the ethanol generated by the hydrolysis of tetraethyl orthosilicate. Note that water needs to be added continuously during the process to keep the total mass constant. After that, transfer the solution to a polytetrafluoroethylene-lined autoclave and hydrothermally heat it for 48 h to crystallize it. After crystallization, filter and wash with deionized water until neutral, place it at 80 °C to dry overnight, grind it into powder, and calcine it in air atmosphere at 550 °C at a heating rate of 2 °C / min for 6 h to obtain Silicalite-1 molecular sieve.
[0027] 3 g of Silicalite-1 molecular sieve, 10.17 g of tetrapropylammonium hydroxide and 30.50 mL of water were mixed and stirred at room temperature for 2 h. The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and hydrothermaled at 170 °C for 3 h to obtain a precursor sol. After cooling to room temperature, an aqueous solution containing 0.0720 g of Fe(NO3)3·9H2O was slowly introduced into the precursor sol and stirred at room temperature for 3 h. The precursor sol was then transferred to a polytetrafluoroethylene-lined autoclave and dynamically hydrothermaled at 200 °C for 48 h (equipment: Yamato Constant Temperature Oven DKN312C, Japan). After the reaction, the product was washed with water several times and centrifuged to neutrality, dried at 80 °C overnight, and then ground into powder. It was calcined at 550 °C in air atmosphere at a heating rate of 2 °C / min for 6 h to obtain a 0.5Fe-MFI catalyst (where the Fe content was 0.5 wt%).
[0028] Example 2 0.3Fe-MFI The synthesis steps of Silicalite-1 molecular sieve are the same as those in Example 1. 3 g of Silicalite-1 molecular sieve, 10.17 g of tetrapropylammonium hydroxide and 30.50 mL of water were mixed and stirred at room temperature for 2 h. The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and hydrothermaled at 170 °C for 3 h to obtain a precursor sol. After cooling to room temperature, an aqueous solution containing 0.0432 g of Fe(NO3)3·9H2O was slowly introduced into the precursor sol and stirred at room temperature for 3 h and then transferred to a polytetrafluoroethylene-lined autoclave for dynamic hydrothermal heating at 200 °C for 48 h (equipment: Japan Yamato Constant Temperature Oven DKN312C). Finally, after multiple water washing and centrifugation to neutrality, it was placed at 80 °C for drying overnight and ground into powder, and calcined at 550 °C in air atmosphere at a heating rate of 2 °C / min for 6 h to obtain a 0.3Fe-MFI catalyst (wherein the Fe content is 0.3wt%).
[0029] Example 3 1.2Fe-MFI The synthesis steps of Silicalite-1 molecular sieve are the same as those in Example 1. 3g of Silicalite-1 molecular sieve, 10.17g of tetrapropylammonium hydroxide and 30.50mL of water were mixed and stirred at room temperature for 2h. The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and hydrothermally heated at 170 °C for 3 h to obtain a precursor sol. After cooling to room temperature, an aqueous solution containing 0.1728g of Fe(NO3)3·9H2O was slowly introduced into the precursor sol and stirred at room temperature for 3 h and then transferred to a polytetrafluoroethylene-lined autoclave for dynamic hydrothermal heating at 200 °C for 48 h (equipment: Japan Yamato Constant Temperature Oven DKN312C). Finally, after multiple water washing and centrifugation to neutrality, it was placed at 80 °C for drying overnight and ground into powder, and calcined at 550 °C in air atmosphere at a heating rate of 2 °C / min for 6 h to obtain a 1.2Fe-MFI catalyst (wherein the Fe content is 1.2wt%).
[0030] Example 4 1.5Fe-MFI The synthesis steps of Silicalite-1 molecular sieve are the same as those in Example 1. 3g of Silicalite-1 molecular sieve, 10.17g of tetrapropylammonium hydroxide and 30.50mL of water were mixed and stirred at room temperature for 2h. The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and hydrothermally heated at 170 °C for 3h to obtain a precursor sol. After cooling to room temperature, an aqueous solution containing 0.2160g of Fe(NO3)3·9H2O was slowly introduced into the precursor sol and stirred at room temperature for 3h and then transferred to a polytetrafluoroethylene-lined autoclave for dynamic hydrothermal heating at 200 °C for 48h (equipment: Japan Yamato Constant Temperature Oven DKN312C). Finally, after multiple water washing and centrifugation to neutrality, it was placed at 80 °C for drying overnight and ground into powder, and calcined in air atmosphere at 550 °C at a heating rate of 2 °C / min for 6h to obtain a 1.5Fe-MFI catalyst (wherein the Fe content is 1.5 wt%).
[0031] Example 5 0.5Fe-MFI-FeCl3 The synthesis steps of Silicalite-1 molecular sieve are the same as those in Example 1. 3g of Silicalite-1 molecular sieve, 10.17g of tetrapropylammonium hydroxide and 30.50mL of water were mixed and stirred at room temperature for 2h. The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and hydrothermaled at 170 °C for 3h to obtain a precursor sol. After cooling to room temperature, an aqueous solution containing 0.048g of FeCl3·6H2O was slowly introduced into the precursor sol and stirred at room temperature for 3h and then transferred to a polytetrafluoroethylene-lined autoclave for dynamic hydrothermal heating at 200 °C for 48h (equipment: Japan Yamato Constant Temperature Oven DKN312C). Finally, after multiple water washing and centrifugation to neutrality, it was placed at 80 °C for drying overnight and ground into powder, and calcined at 550 °C in air atmosphere at a heating rate of 2 °C / min for 6h to obtain a 0.5Fe-MFI-FeCl3 catalyst (wherein the content of Fe is 0.5 wt%).
[0032] Example 6 0.5Fe-BEA 1.5 g of sodium hydroxide, 0.075 g of silicon dioxide seed, 5.9 g of tetraethylammonium hydroxide and 7.5 g of fumed silica were added to a mortar in sequence, mixed evenly and ground for 30 min, and then the resulting powder was transferred to a polytetrafluoroethylene-lined autoclave for hydrothermal treatment at 145 °C for 16 h. After that, it was washed with deionized water until neutral, dried overnight at 110 °C, and ground to powder. 5 g of the above powder and 100 g of 1.0 mol / L ammonium nitrate solution were weighed and ion exchanged in a 90 °C water bath for 3 h, centrifuged and washed with deionized water 3 times, dried overnight at 80 °C, and ground into powder, and calcined in air atmosphere at 550 °C at a heating rate of 2 °C / min for 6 h to obtain pure Si BEA molecular sieve.
[0033] 3g pure Si BEA molecular sieve, 7.36g tetraethylammonium hydroxide and 30.60 mL water were mixed and stirred at room temperature for 2h. The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and hydrothermaled at 170 °C for 3h to obtain a precursor sol. After cooling to room temperature, an aqueous solution containing 0.072 g Fe(NO3)3·9H2O was slowly introduced into the precursor sol and stirred at room temperature for 3h and then transferred to a polytetrafluoroethylene-lined autoclave for dynamic hydrothermal heating at 200 °C for 48h (equipment: Japan Yamato Constant Temperature Oven DKN312C). Finally, it was washed with water and centrifuged to neutrality several times, dried at 80 °C overnight, and then ground into powder. It was calcined at 550 °C in air atmosphere at a heating rate of 2 °C / min for 6h to obtain a 0.5Fe-BEA catalyst (where the Fe content is 0.5 wt%).
[0034] Example 7 0.5Fe-CHA 1.06 g N,N,N-trimethyladamantane ammonium hydroxide and 5.4 g water were mixed and stirred evenly, 6 g fumed silica was slowly added and stirred for 30 min, and aged at room temperature for 24 h. 0.1 g hydrofluoric acid was slowly added dropwise while stirring. The obtained gel was then transferred to a polytetrafluoroethylene-lined autoclave and dynamically hydrothermally heated at 150 °C for 48 h (equipment: Japan Yamato Constant Temperature Oven DKN312C). After the hydrothermal treatment, it was washed with water several times and centrifuged to neutrality, dried at 100 °C overnight, and then ground into powder. It was calcined in air atmosphere at 700 °C at a heating rate of 1 °C / min for 8 h to obtain pure Si CHA molecular sieve.
[0035] 3g pure Si CHA molecular sieve, 10.57g N,N,N-trimethyladamantane ammonium hydroxide and 31.70mL water were mixed and stirred at room temperature for 2h. The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and hydrothermaled at 170 °C for 3h to obtain a precursor sol. After cooling to room temperature, an aqueous solution containing 0.0720g Fe(NO3)3·9H2O was slowly introduced into the precursor sol and stirred at room temperature for 3h and then transferred to a polytetrafluoroethylene-lined autoclave for dynamic hydrothermal heating at 200 °C for 48h (equipment: Japan Yamato Constant Temperature Oven DKN312C). Finally, it was washed with water several times and centrifuged to neutrality, dried at 80 °C overnight, and then ground into powder. It was calcined at 550 °C in air atmosphere at a heating rate of 2 °C / min for 6h to obtain 0.5Fe-CHA catalyst (where the Fe content is 0.5 wt%).
[0036] Comparative Example 1 0.5Fe / MFI-IWI The synthesis steps of Silicalite-1 molecular sieve are the same as those in Example 1. 0.036 g of Fe(NO3)3·9H2O was dissolved in 600 μL of water and ultrasonicated for 15 min, and then impregnated into 1 g of Silicalite-1 molecular sieve in equal volume, aged at room temperature for 3 h, and then dried at 80°C overnight. After sufficient grinding, the mixture was calcined at 550°C in air atmosphere for 6 h at a heating rate of 2°C / min to obtain a 0.5Fe / MFI-IWI catalyst (wherein the Fe content was 0.5 wt%).
[0037] Comparative Example 2 0.5Fe / ZSM-5-IWI After 6.23 g of tetrapropylammonium hydroxide and 83.75 g of water were mixed and stirred evenly, 25.51 g of tetraethyl orthosilicate was slowly added dropwise and stirred until it was clear and transparent, and then 0.34 g of sodium aluminate was added and stirred for 30 min. Then, the above solution was placed in a 50 °C water bath and stirred for 30 min, and then the temperature was raised to 80 °C and stirred continuously to drive away the ethanol generated by the hydrolysis of tetraethyl orthosilicate. Note that water needs to be added continuously during the process so that the total mass remains unchanged. After that, the solution was transferred to a polytetrafluoroethylene-lined autoclave and hydrothermally heated for 72 h to crystallize it. After crystallization, it was filtered and washed with deionized water until neutral, placed at 80 °C for drying overnight, and then ground into powder, and calcined in an air atmosphere at 550 °C at a heating rate of 2 °C / min for 6 h. Weigh 5 g of the above-prepared powder and pour it into 100 mL of 1 mol / L ammonium nitrate solution, stir it in a water bath at 80 °C for 2 h, and then centrifuge it, and repeat this 3 times. The solid after centrifugation was dried at 80 °C overnight and then ground into powder, and calcined in air atmosphere at 550 °C for 6 h at a heating rate of 2 °C / min to obtain ZSM-5 (Si:Al=30) molecular sieve.
[0038] 0.036 g Fe(NO3)3·9H2O was dissolved in 600 μL water and ultrasonicated for 15 min, and then impregnated into 1 g ZSM-5 (Si:Al=30) molecular sieve with equal volume, aged at room temperature for 3 h, and then dried at 80 °C overnight. After sufficient grinding, it was calcined at 550 °C in air atmosphere for 6 h at a heating rate of 2 °C / min to obtain 0.5Fe / ZSM-5-IWI catalyst (with Fe content of 0.5 wt%).
[0039] Figure 1The XRD diagrams of the catalysts obtained in Example 1 and Comparative Example 1 are shown in the figure. As can be seen from the figure, both Example 1 and Comparative Example 1 are consistent with the MFI configuration standard card, indicating that the introduction of Fe will not change the molecular sieve crystal structure. In addition, no relevant diffraction characteristic peaks of Fe species were detected in all catalysts, which may be caused by the Fe species being below the XRD detection limit.
[0040] Figure 2 The UV-Vis images of the catalysts obtained in Example 1 and Comparative Example 1 show that a large amount of oligomeric Fe x O y species (350-500 nm) and aggregated Fe2O3 particles (>500 nm); 0.5Fe-MFI (Example 1) has no obvious aggregation phenomenon, and most of the isolated Fe 3+ species (<250 nm) and isolated Fe 3+ Species (250-350 nm) exist. This shows that the Fe species in Example 1 enter the molecular sieve framework and the molecular sieve pores, with good dispersion effect and no aggregation.
[0041] Figure 3 TEM images of the catalysts obtained in Example 1 (A) and Comparative Example 1 (B). As can be seen from the figure, the surface of the 0.5Fe-MFI (Example 1) catalyst is smooth with a clear square outline, and no nanoparticles of Fe species are observed, indicating that Fe has good dispersion on the catalyst. Further from the mapping, Si, O, and Fe are evenly distributed, and there is no aggregation of Fe species and most of them are inside the molecular sieve. However, 0.5Fe / MFI-IWI is square but the surface is not smooth and has a slightly elliptical morphology. Fe can be observed on the surface. x O y From the mapping, Si and O are evenly distributed, but Fe species are obviously aggregated on the catalyst surface, indicating that 0.5Fe / MFI forms Fe species oligomers or clusters.
[0042] Figure 4 The CH4-TPD diagram of the catalysts obtained in Example 1 and Comparative Example 1. It can be seen from the figure that the characteristic absorption peak position of the catalyst of 0.5Fe / MFI-IWI (Comparative Example 1) is at 92 o C, the peak area is small, indicating that 0.5Fe / MFI is difficult to adsorb a large amount of methane. In contrast, the characteristic absorption peak position of the 0.5Fe-MFI (Example 1) catalyst is at 122 oC, the peak area is much larger than that of 0.5Fe / MFI-IWI, which indicates that 0.5Fe-MFI exhibits good adsorption performance for methane and can provide more methane adsorption sites.
[0043] The catalysts synthesized in the above examples and comparative examples were used to synthesize formic acid.
[0044] Application Example 1 20 mg 0.5Fe-MFI catalyst, 15 mL water and 0.5667 g hydrogen peroxide (30% aqueous solution) were put into a 50 mL batch reactor, filled with 1 MPa methane gas, and reacted at 70 °C for 30 min. The reaction results are shown in Table 1.
[0045] Application Example 2 20 mg 0.5Fe-MFI catalyst, 15 mL water and 0.5667 g hydrogen peroxide (30% aqueous solution) were put into a 50 mL batch reactor, filled with 2 MPa methane gas, and reacted at 70 °C for 30 min. The reaction results are shown in Table 1.
[0046] Application Example 3 20 mg 0.5Fe-MFI catalyst, 15 mL water and 0.5667 g hydrogen peroxide (30% aqueous solution) were put into a 50 mL batch reactor, filled with 3 MPa methane gas, and reacted at 70 °C for 30 min. The reaction results are shown in Table 1.
[0047] Application Example 4 20 mg 0.5Fe-MFI catalyst, 15 mL water and 0.5667 g hydrogen peroxide (30% aqueous solution) were put into a 50 mL batch reactor, filled with 4 MPa methane gas, and reacted at 70 °C for 30 min. The reaction results are shown in Table 1.
[0048] Application Example 5 20 mg 0.3Fe-MFI catalyst, 15 mL water and 0.5667 g hydrogen peroxide (30% aqueous solution) were put into a 50 mL batch reactor, filled with 2 MPa methane gas, and reacted at 70 °C for 30 min. The reaction results are shown in Table 1.
[0049] Application Example 6 20 mg 1.2Fe-MFI catalyst, 15 mL water and 0.5667 g hydrogen peroxide (30% aqueous solution) were put into a 50 mL batch reactor, filled with 2 MPa methane gas, and reacted at 70 °C for 30 min. The reaction results are shown in Table 1.
[0050] Application Example 7 20 mg 1.5Fe-MFI catalyst, 15 mL water and 0.5667 g hydrogen peroxide (30% aqueous solution) were put into a 50 mL batch reactor, filled with 2 MPa methane gas, and reacted at 70 °C for 30 min. The reaction results are shown in Table 1.
[0051] Application Example 8 20 mg 0.5Fe-MFI-FeCl3 catalyst, 15 mL water and 0.5667 g hydrogen peroxide (30% aqueous solution) were put into a 50 mL batch reactor, filled with 2 MPa methane gas, and reacted at 70 °C for 30 min. The reaction results are shown in Table 1.
[0052] Application Example 9 20 mg 0.5Fe-BEA catalyst, 15 mL water and 0.5667 g hydrogen peroxide (30% aqueous solution) were placed in a 50 mL batch reactor, filled with 2 MPa methane gas, and reacted at 70 °C for 30 min. The reaction results are shown in Table 1.
[0053] Application Example 10 20 mg 0.5Fe-CHA catalyst, 15 mL water and hydrogen peroxide (30% aqueous solution) were put into a 50 mL batch reactor, filled with 2 MPa methane gas, and reacted at 70 °C for 30 min. The reaction results are shown in Table 1.
[0054] Application Comparative Example 1 20 mg 0.5Fe / MFI-IWI catalyst, 15 mL water and hydrogen peroxide (30% aqueous solution) were put into a 50 mL batch reactor, filled with 2 MPa methane gas, and reacted at 70 °C for 30 min. The reaction results are shown in Table 1.
[0055] Application Comparative Example 2 20 mg 0.5Fe / ZSM-5-IWI catalyst, 15 mL water and hydrogen peroxide (30% aqueous solution) were put into a 50 mL batch reactor, filled with 2 MPa methane gas, and reacted at 70 °C for 30 min. The reaction results are shown in Table 1.
[0056] Table 1 Experimental results of methane oxidation to formic acid in application examples and comparative examples As can be seen from the table, the space-time yield and selectivity of the catalyst synthesized by the equal volume impregnation method (comparative examples 1 and 2) for preparing formic acid are lower than those of Examples 1-10, indicating that the catalyst synthesized by the preparation method has high activity in the technology of preparing formic acid by selective oxidation of methane. At the same time, the Fe metal itself can be used to simultaneously improve the methane adsorption sites and methane activation sites without introducing a second auxiliary metal.
[0057] Figure 5 The XRD diagrams before and after the reaction of the catalyst obtained in Example 1 are shown. From the diagram, it can be seen that the catalyst after the reaction can also maintain the MFI configuration, and no relevant diffraction characteristic peaks of Fe species are observed.
[0058] Figure 6 The UV-Vis images before and after the reaction of the catalyst obtained in Example 1 are shown. No oligomeric iron oxide and iron oxide agglomeration were observed in the catalyst after the reaction, and the peak distribution of the original catalyst remained basically unchanged, indicating that the Fe species in the catalyst after the reaction can better maintain the original state.
[0059] Figure 7 This is a cycle stability evaluation diagram of the catalyst obtained in Example 1. It can be seen from the figure that the catalytic activity of each cycle can be maintained at a certain level, and the formic acid selectivity is greater than 90%, indicating that the catalyst has good cycle stability.
[0060] The above specific embodiments are further explanations of the technical solutions and beneficial effects of the present invention, and are not limitations on the implementation methods. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing an Fe-based catalyst for synthesizing formic acid under mild conditions, characterized in that: The steps include: (1) Pure Si molecular sieve, template and water are mixed, subjected to high temperature hydrothermal treatment to obtain a precursor sol, and then cooled to room temperature; (2) slowly introducing an aqueous solution containing an Fe source into the precursor sol, stirring it evenly, and then subjecting it to high-temperature dynamic hydrothermal treatment for crystallization again; (3) The precipitate obtained in step (2) is centrifuged, washed and dried, ground into powder and then calcined in a high temperature atmosphere to obtain an Fe-based catalyst.
2. The preparation method according to claim 1, characterized in that: The topological structure of the pure Si molecular sieve in step (1) is any one of MFI, BEA and CHA.
3. The preparation method according to claim 1, characterized in that: The template agent in step (1) is one of tetrapropylammonium hydroxide, tetraethylammonium hydroxide and N,N,N-trimethyladamantaneammonium hydroxide.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the pure Si molecular sieve, the template and water in step (1) is 1: (0.2-2.0): (10-50).
5. The preparation method according to claim 1, characterized in that: The hydrothermal treatment temperature in step (1) is 100-230 o C, the hydrothermal treatment time is 3-6 h.
6. The preparation method according to claim 1, characterized in that: The dynamic hydrothermal treatment temperature in step (2) is 140-230 o C, the hydrothermal treatment time is 24-72 h.
7. The preparation method according to claim 1, characterized in that: The Fe source in step (2) is one of Fe(NO3)3·9H2O, FeCl3·6H2O or EDTA-Fe.
8. The preparation method according to claim 1, characterized in that: The calcination temperature in step (3) is 450-900°C and the calcination time is 6-12 h.
9. The Fe-based catalyst obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The Fe content in the Fe-based catalyst is 0.1-1.5 wt %.
10. Use of the Fe-based catalyst as claimed in claim 9 in the selective oxidation of methane to synthesize formic acid.
Citation Information
Patent Citations
Preparation method of catalyst with Fe nanoparticles inlaid into hierarchical pore molecular sieve crystal particles
CN107176613A
Oxidative conversion of methane to oxygenates
CN108602741A
Synthesis method and application of pure silicon MWW molecular sieve
CN113880102A
Hierarchical porous Fe / ZSM-5 molecular sieve and preparation method and application thereof
CN114405538A
Method for preparing oxygen-containing organic compound by activating methane at low temperature
CN114621054A
Cited By
Fe-CHA catalyst, preparation method thereof and methane partial oxidation method
CN121927673A